From Sin To Innovation: Ethical And Legal Reflections On Human Weakness In Islamic Perspective - Ekawati; Andi Fika Widuri (Tunas Harapan Ummat Foundation, 2025)
Human imperfection has long been acknowledged in Islamic moral philosophy, yet its constructive potential in shaping legal-ethical innovation remains critically underexplored. This transformative process arises from the self-reflective nature of weakness itself, as the awareness of limitation compels intellectual introspection and moral creativity. Previous studies often treat moral deviation, conceptualized as ma‘ṣiyah (sin), solely as a theological failure rather than a generative moral energy. This study aims to reconceptualize human weakness not as a liability but as a catalyst for ethical and juridical creativity within the Islamic civilizational framework. This paper does not romanticize sin, but situates it within a theological framework of repentance and ethical renewal under divine guidance. Using a qualitative and integrative methodology that combines hermeneutic analysis of classical fiqh and akhlaq manuscripts with normative reflection on contemporary digital ethics, this research develops a multidimensional model bridging theology, ethics, and law, an analytical configuration rarely attempted in previous Islamic scholarship. The findings reveal a transformative dialectic: when moral failure is internalized through repentance (tawbah): when moral failure is internalized through repentance (tawbah) and an ethical form of critical reflection (ijtihād al-nafs), it produces renewed ethical consciousness and legal adaptability (tajdīd) responsive to social transformation. As articulated by al-Ghazālī in Kitāb al-Tawbah, repentance transforms error into a moral awakening that sustains intellectual and civilizational renewal. This paper contributes a new conceptual articulation of how Islamic ethical and legal systems transform human fallibility into a driver of intellectual vitality, digital ethics, and civilizational resilience, offering an alternative epistemological foundation for understanding innovation within Islamic heritage. In doing so, this study offers a dynamic and constructive re-evaluation of human weakness in the context of contemporary digital ethics.